The Effect of Perceived Product Quality, Brand Personality, and Loyalty on Brand Switching Intention of Technological Products - Hanifati, Lidya Nur; Salehudin, Imam (UI Scholars Hub, 2021)
Research Aims: Laptops are essential in people's everyday lives. Since laptop utilization has been very high during the COVID-19 pandemic because of the restrictions imposed by the pandemic, many laptop manufacturers have made efforts to drive consumers to switch to their laptop brands. The main objective of this research is to examine how perceived product quality, brand personality, and loyalty affect brand switching intention. Design/methodology/approach: The data were collected online from 216 consumers. Structural Equation Modelling (SEM) was employed to analyse the data. Research Findings: The result demonstrates that perceived product quality, brand personality, and loyalty have both direct and indirect negative effects on consumers' switching intention. It is revealed that variables play a pivotal role in consumers' evaluation of laptop products and their subsequent switching intention. Theoretical Contribution/Originality: There is currently a dearth of studies testing the impact of brand personality dimensions on consumer brand identification, perceived product quality, loyalty, and switching intention. Our findings provide more insight into switching intention as a means to achieve a competitive edge in global laptop shipments during the Covid-19 pandemic. Managerial Implications in the South East Asian context: This study can serve as a comprehensive guideline for businesses to position their brands successfully to reduce any consumer switching intentions affecting their products. However, consumers' perspectives on brand personality with a laptop product affect their critical evaluations. Global laptop manufacturers should leverage brand personality to engender positive consumer evaluation and reduce switching intention. Research Limitations & Implications: Other factors beyond the scope of the research, such as brand-related factors, have many different inherent attributes (e.g., specifications, functions, designs, prices, and advancements) whose influence on switching intention needs to be considered in future research.